(untitled) (TAJ: Journal of Teachers Association, 2019)
The study was done to observe whether there is any association of pneumonia with hyponatraemia, as well as to have a view to the patients’ hospital-stay in this regard. This study was conducted from July 2009 to September 2011 at the Department of Biochemistry of Shaheed Ziaur Rahman Medical College (SZMC), Bogra. Total 35 cases, 1 month to 5 years of age, who suffered from pneumonia, were included in this study. Their serum Na+, K+& Cl- levels were measured and their hospital stays in days were recorded for the comparison between normonatraemics and hyponatraemics. The distribution patterns were described as percentage of total. In addition, Student’s ‘t’ test and Pearson’s correlation co-efficient test were also used. Among 35 cases, 22 (63%) cases were male and 13 (37%) cases were female; 14 (40%) cases were hyponatraemic and 21 (60%) cases were normonatraemic. Mean (±SD) of age was 19.6 (±15.2) months. For all the cases, there was a positive correlation of serum Cl– with serum Na+ levels (p<0.001); but no correlation was observed between serum K+& Na+ levels (P>0.10). Hospital stay of hyponatraemic cases was higher than the normonatraemic cases (P<0.05). Children with pneumonia may develop hyponatraemia, which if not managed in due time, may lead to delayed recovery from illness. TAJ 2018; 31(2): 59-62